Flexible conductive fabric/E‐glass fibre composite ultra‐wideband antenna for future wireless networks. Issue 4 (19th February 2019) - Elmobarak, Husameldin Abdelrahman; Rahim, Sharul Kamal Abdul; Castel, Xavier; Himdi, Mohamed
Abstract : This study highlights the integration potential of a highly conductive fabric into composite materials based on an efficient fabrication technology for coplanar waveguide flexible composite ultra‐wideband antenna radiating from 3.3 to 12 GHz. A thin sheet of a highly conductive fabric has been embedded by infusion process in a thin composite laminate made of E‐glass fibre mat and epoxy resin to fabricate a flexible conductive composite laminate. The antenna elements have been machined precisely by laser etching. The measured radiation efficiency reaches over 70% throughout the antenna operating frequency band with satisfactory radiation patterns and gain. The composite antenna exhibits reliable performance under different bending conditions as presented by the measurements. The high radiation performance, the seamless integration process and flexible mechanical properties of such composite antennas pave the way for their promising potential for integrating efficient antennas into various devices and objects made of composite laminate materials.